Promoting Malaysian Architecture Through QR-Integrated Enamel Pin Merchandise - Ismail, Nurhana; Kamaruddin, Norfadilah (Research in Management of Technology and Business, 2026)
Malaysian architecture, encompassing traditional and modern structures, plays an important role in the nation’s cultural identity. However, increasing modernization and a lack of awareness, particularly among younger generations and tourists, threaten its appreciation and preservation. This decline not only impacts cultural heritage but also affects economic sustainability. This study explores the potential of wearable merchandise as an innovative tool for promoting Malaysian architecture. Specifically, it examines the role of civil servants in fostering cultural appreciation by incorporating architectural-themed wearable merchandise into their daily attire. The research aims to assess their awareness of Malaysia’s architecture and propose merchandise designs that effectively represent and promote these landmarks. A quantitative survey was conducted to analyse awareness, preferences, and attitudes toward wearable merchandise inspired by Malaysian architecture. The findings inform the design of impactful accessories that serve as everyday reminders of architectural significance. By integrating such merchandise into professional settings, this study will present an accessible and sustainable approach to enhancing cultural appreciation.